Al-Ḥikmah Perspektif M. Quraish Shihab dalam Tafsir Al-Mishbah - Muhammad Fauzan Akmal; Mardan; Abdul Ghany (LPPM IAIN Sorong, 2026)
This study examines the concept of al-ḥikmah in Tafsir al-Mishbah by M. Quraish Shihab, motivated by the tendency to reduce al-ḥikmah to passive acceptance rather than understanding it as a principle of sound judgment and beneficial action. The research aims to analyze the essence, existence, and urgency of al-ḥikmah from Quraish Shihab’s perspective. This study employs a qualitative library research method using a thematic (maudhu‘i) approach, supported by tahlili, comparative, linguistic, and historical approaches. The primary data consist of Qur’anic verses containing the term al-ḥikmah and their interpretations in Tafsir al-Mishbah, while secondary data are derived from relevant books, journal articles, and other scholarly works. The findings reveal that al-ḥikmah in Tafsir al-Mishbah is classified into three principal meanings: (1) Prophetic tradition and prophethood, (2) true knowledge integrated with its proper implementation (al-'ilm al-'amali and al-'amal al-'ilmi), and (3) wisdom or practical competence in achieving benefit and preventing harm. Furthermore, al-ḥikmah serves as an essential foundation for understanding the Qur’an, integrating knowledge with action, guiding sound decision-making, and shaping individuals who embody Qur’anic values in contemporary life.